Spatial and temporal structure of diversity and demographic dynamics along a successional gradient of tropical forests in southern Brazil. Issue 7 (13th March 2020) - Dalmaso, Cilmar Antônio; Marques, Marcia C. M.; Higuchi, Pedro; Zwiener, Victor P.; Marques, Renato
Abstract: Analysis of the structure, diversity, and demographic dynamics of tree assemblages in tropical forests is especially important in order to evaluate local and regional successional trajectories. We conducted a long‐term study to investigate how the structure, species richness, and diversity of secondary tropical forests change over time. Trees (DBH ≥ 5 cm) in the Atlantic Forest of southern Brazil were sampled twice during a 10‐year period (2007 and 2017) in six stands (1 ha each) that varied in age from their last disturbance (25, 60, 75, 90, and more than 100 years). We compared forest structure (abundance and basal area), species richness, alpha diversity, demographic rates (mortality, recruitment, and loss or gain in basal area), species composition, spatial beta diversity, and temporal beta diversity (based on turnover and nestedness indices) among stand ages and study years. Demographic rates recorded in a 10‐year interval indicate a rapid and dynamic process of species substitution and structural changes. Structural recovery occurred faster than beta diversity and species composition recovery. The successional gradient showed a pattern of species trade‐off over time, with less spatial dissimilarity and faster demographic rates in younger stands. As stands grow older, they show larger spatial turnover of species than younger stands, making them more stochastic in relation to species composition. Stands appear to split chronologically to some extent, but not across a straightforward linear axis, reflecting stochastic changes, providing evidence for the formation of a nonequilibrium community. Policy implications . These results reiterate the complexity and variability in forest succession and serve as a reference for the evaluation and monitoring of local management and conservation actions and for defining regional strategies that consider the diversity of local successional trajectories to evaluate the effectiveness of restoration measures in secondary forests of the Atlantic Forest biome. Abstract : A long‐term study of changes in the structure and diversity of secondary forests. Effects of partitioning beta diversity of tropical secondary forests in Brazil. Reference work for the monitoring of recovery actions in tropical ecosystems.